Identification and characterization of miRNAs during early pregnancy in domestic sheep - Pokharel, Kisun; Peippo, Jaana; Li, Meng‐Hua; Kantanen, Juha (Published by Blackwell Scientific for the International Society for Animal Blood Group Research, 2020)
MicroRNA resources in sheep are limited compared with those in other domesticated mammalian species. By sequencing small RNAs of sheep corpus luteum and endometrium, we have generated the largest amount of miRNA-seq data and compiled the most comprehensive list thus far of miRNAs (n = 599) in sheep. Additionally, we observed a highly conserved maternally imprinted cluster of miRNAs on chromosome 18 homologous to that found on chromosome 14 in human and several other eutherian mammals.
Keywords: corpus luteum; endometrium; Finnsheep; Texel